Scientific Activity of the Faculty of Canon Law in 1954-2019 - DZIERŻON, GINTER (Prawo Kanoniczne, 2019)
The presented study is a ceremonial lecture given on the occasion of the 65th anniversary of the scientific activity of the Faculty of Canon Law. The author presented the following thematic topics: short history of the faculty, main directions of scientific research, academic achievements of the faculty's employees, staff scientific meetings, canonist lectures, honoris causa doctorates and other forms of activity.